(untitled) (Web of Teachers: Inderscience Research, 2024)
The article covers the history of the pilgrimage place Shoabdumalik-ota, located in the Akhangaran district of the Tashkent region, as well as its restoration by the international charitable foundation “Oltin Meros” (‘Golden Heritage’) and its activities today. The authors express their views on the role and importance of the pilgrimage place Shoabdumalik-ota in the development of pilgrimage tourism in our country.